2002
DOI: 10.1139/z02-118
|View full text |Cite
|
Sign up to set email alerts
|

Response to acute stress in the Harlequin Duck (Histrionicus histrionicus) during the breeding season and moult: relationships to gender, condition, and life-history stage

Abstract: Seasonal adjustments and individual responses to environmental perturbations have been well characterized in many passerine species but similar studies in other groups of birds are sparse. Larger-bodied and longer-lived avian species have different life-history strategies and different energy-storage and -utilization patterns. We investigated the response to capture stress in male and female Harlequin Ducks (Histrionicus histrionicus) during the breeding season on montane rivers and during moult on coastal wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Many studies have found negative correlations between aspects of body size (e.g. body mass, body condition) and baseline and/or stress-induced corticosterone (Schoech et al, 1997;Kitaysky et al, 1999;Moore et al, 2000;Romero and Wikelski, 2001;Perfito et al, 2002). Our failure to detect a significant correlation between morphology and corticosterone concentrations in ducklings at 2 days post-hatching may reflect the small range of body sizes at this age.…”
Section: Discussionmentioning
confidence: 58%
“…Many studies have found negative correlations between aspects of body size (e.g. body mass, body condition) and baseline and/or stress-induced corticosterone (Schoech et al, 1997;Kitaysky et al, 1999;Moore et al, 2000;Romero and Wikelski, 2001;Perfito et al, 2002). Our failure to detect a significant correlation between morphology and corticosterone concentrations in ducklings at 2 days post-hatching may reflect the small range of body sizes at this age.…”
Section: Discussionmentioning
confidence: 58%
“…Increased CORT levels have also been found to be negatively related to body condition (Schwabl, 1995;Hood et al, 1998;Kitaysky et al, 2001;Sockman and Schwabl, 2001;Perfito et al, 2002;Breuner and Hahn, 2003;Pereyra and Wingfield, 2003;Love et al, 2005;Perez-Rodriguez et al, 2006;Roberts et al, 2007a). However, some studies have found no relationship between either CORT (Lormee et al, 2003;Lynn et al, 2003) or T (Buttemer and Astheimer, 2000;AlonsoAlvarez et al, 2002) and body condition.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to suggest that high levels of CORT may have a negative effect on body condition in birds (Schwabl, 1995;Hood et al, 1998;Kitaysky et al, 2001;Sockman and Schwabl, 2001;Perfito et al, 2002;Breuner and Hahn, 2003;Pereyra and Wingfield, 2003), and this may affect the quality of male sexual signals. This negative relationship between sexual signal quality and CORT level has been found previously (see Saino et al, 2002).…”
Section: Introductionmentioning
confidence: 99%